Psychometric Properties of the Brief Resilience Scale Among Alternative Sexuality Community Members - Kaniuka, Andréa R. (Journal of interpersonal violence, 2023)
Assessing resilience among alternative sexuality (alt-sex; e.g., kink, polyamory) community members is imperative as alt-sex individuals often face discrimination and possess intersecting marginalized identities. The Brief Resilience Scale (BRS) has extensive psychometric support; however, prior research indicates both a one- and two-factor (i.e., succumbing and resilience) structure. Further, the psychometric properties of the BRS have not been examined among alt-sex community members. As such, the current study examined the BRS factor structure among alt-sex individuals and measurement invariance across demographic groups (i.e., sexual orientation, gender identity, and sexual assault history). Confirmatory factor analyses and multi-groups invariance analyses were conducted. The two-factor BRS model demonstrated better fit to the data. Model fit did not differ by sexual orientation or gender identity. Measurement invariance was observed by lifetime sexual assault history, with higher factor loadings on succumbing items among alt-sex community members with a lifetime history of sexual assault. Our findings support use of the BRS to measure resilience among alt-sex individuals. Succumbing, or weakened resilience, is a salient factor for alt-sex community members who are sexual assault survivors, warranting further attention.